Implementation of Maqashid Syariah on Cash Waqf Linked Sukuk - Maulidia Alfian, Annisa; Syafitri, Helin; Permata Sari, Indah; Tiswarni, Tiswarni (Iqtishodia: Jurnal Ekonomi Syariah, 2025)
This research aims to analyze the implementation of maqashid syariah in Cash Waqf Linked Sukuk (CWLS) and assess the alignment of the CWLS instrument towards public benefit. The theories used are the theory of waqf, cash waqf and maqashid syariah. This research is qualitative research with a literature review method. The research stages in order to analyze the implementation of maqashid syariah in CWLS are the preparation stage, literature collection, analysis and conclusion stages. The results of this research show that the concept and implementation of CWLS has implemented maqashid sharia both directly and indirectly. In hifzh ad-din, the implementation of CWLS has received a statement of sharia conformity by the DSN MUI. At hifzh an-nafs, CWLS investment proceeds have been allocated to hospitals which have served thousands of people to recover from their illnesses. At hifzh al-aql, one of the CWLS investment return fund allocations was given to the educational project funding program, so that it has facilitated many students to obtain knowledge and education. In the hifzh an-nasl concept, indirectly the implementation of CWLS has been allocated for long-term social and infrastructure projects so that the benefits can be felt by the next generation. Finally, in the hifzh al-mal concept, the implementation of CWLS has an economic value that provides returns on investment, this economic value can be enjoyed by mauquf alaih and other stakeholders.